The Implications Of The War On Syria At Economic Growth (2011-2020) - الدعاس, بشير (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The war on Syria has severely damaged the stock of physical and human capital. This study evaluates the implications of the war on economic growth in Syria by comparing the factors affecting economic growth before and during the crisis, perhaps the most prominent of which are the lack of funding, the high unemployment rate, and the decrease in the exchange rate of the Syrian Pound, as an indicator of high prices and economic inflation, which resulted in the purchasing power of those with limited income, and aggravated the suffering of the population, the main source of power for the economy The Syrian people are the source of the wealth of Syrian society, and the poverty circle has expanded to include 83% of them in 2014 Syria was classified as a fast-growing country before the crisis, but its growth rate declined during the crisis to reach (- 22.5) in 2013. The study concluded that relying on loans as a source of financing is inappropriate and does not match the sustainable debt limit and hinders economic growth in the medium and long term. This research discusses the ability of the Syrian pound to regain its purchasing power, and reached several conclusions, the most prominent of which is that the Syrian pound can regain its purchasing power and its position as soon as the production wheel in the commodity sector begins, and inflation can decline. For this purpose, this research paper proposes adopting a development strategy that takes into account the current reality, the declared international war on Syria, and the brutal siege imposed on its people, taking advantage of the experiences of other countries that have gone through more difficult circumstances than the ones that Syria is going through, and those countries were able to achieve stable and Sustainable economic development.